Evaluating the impact of a curriculum intervention using an assessment rubric for communication skill development of osteopathy students. (March 2023) - Muddle, Lee; O'Malley, Cindy J.; Stupans, Ieva
Abstract: Objective: This paper investigates the impact of a spiral curriculum intervention using a validated assessment rubric for communication skill development of undergraduate osteopathy students. Method: Over a three-year period, students from three cohorts were exposed to zero, one or two semesters of a newly integrated and scaffolded communication curriculum. Using a checklist rubric to collect mean scores and then undertaking comparisons through Pearson chi square analysis, the impact of the curriculum intervention on communication skill development was explored. Results: Cohorts who received zero or two full semesters of communication curriculum performed better (x = 6.34, x = 10.51 respectively) than the cohort who received one (x = 6.03). Conclusion: Despite using an explicit assessment rubric, insufficiently contextualised and integrated curriculum appears to disrupt student learning, whilst a spiralled, scaffolded curriculum delivered at an appropriate level in combination with explicit assessment rubrics work well together to support deeper learning and development. Implications for practice: ∙An insufficiently contextualised and integrated curriculum combined with the frequency of content being re-visited (spiral curriculum) can disrupt the students learning experience. ∙Using a spiralled and scaffolded curriculum significantly improves the development of communication skills. ∙For deeper learning to occur students require a combination of both explicit curriculum and accompanying assessment rubrics.